2013
DOI: 10.1111/dom.12121
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lixisenatide once daily versus placebo in type 2 diabetes insufficiently controlled on pioglitazone (GetGoal‐P)

Abstract: Aims:To compare the efficacy and safety of once-daily prandial lixisenatide with placebo in type 2 diabetes mellitus (T2DM) insufficiently controlled by pioglitazone ± metformin. Methods:This randomized, double-blind study included a 24-week main treatment period and a ≥52-week variable extension period.Patients were randomized 2 : 1 to receive lixisenatide 20 μg once daily or placebo. The primary endpoint was change in glycated haemoglobin (HbA1c) at week 24. Results:In total, 484 patients were randomized: 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
158
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(169 citation statements)
references
References 17 publications
5
158
1
5
Order By: Relevance
“…The combination of GLP-1 receptor agonists and metformin has not been associated with an increase in the rate or severity of clinically relevant hypoglycemic events [32,34,45,46,[115][116][117][118][119][120][121][122]. However, in clinical trials examining GLP-1 receptor agonists in combination with sulphonylurea (with or without metformin) or insulin, the incidence of hypoglycemia, although low overall, was increased compared with placebo ( Table 6, in the Appendix) [32,33,42,[123][124][125][126][127][128][129][130][131][132][133][134][135].…”
Section: Endocrine Effectsmentioning
confidence: 99%
“…The combination of GLP-1 receptor agonists and metformin has not been associated with an increase in the rate or severity of clinically relevant hypoglycemic events [32,34,45,46,[115][116][117][118][119][120][121][122]. However, in clinical trials examining GLP-1 receptor agonists in combination with sulphonylurea (with or without metformin) or insulin, the incidence of hypoglycemia, although low overall, was increased compared with placebo ( Table 6, in the Appendix) [32,33,42,[123][124][125][126][127][128][129][130][131][132][133][134][135].…”
Section: Endocrine Effectsmentioning
confidence: 99%
“…Lixisenatide (Lyxumia ® , Adlyxin ® ; Sanofi, Paris, France) is a once‐daily (QD), prandial, short‐acting GLP‐1 RA that has been evaluated extensively in the large, phase 3 GetGoal clinical trial program carried out in approximately 50 countries including Japan11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21. Treatment with lixisenatide monotherapy in patients with type 2 diabetes mellitus has shown improved glycemic control with reduced HbA1c, postprandial plasma glucose, fasting plasma glucose (FPG) and bodyweight, and has been shown to be well tolerated11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with lixisenatide monotherapy in patients with type 2 diabetes mellitus has shown improved glycemic control with reduced HbA1c, postprandial plasma glucose, fasting plasma glucose (FPG) and bodyweight, and has been shown to be well tolerated11, 12, 13. Lixisenatide has also shown improved glycemic control as an add‐on treatment (including basal insulin with or without SU, metformin, metformin with or without SU, pioglitazone with or without metformin, and SU with or without metformin)12, 14, 15, 16, 17, 18, 19. More specifically, subanalyses of two randomized, placebo‐controlled studies in patients with type 2 diabetes mellitus, GetGoal‐S12 (lixisenatide add‐on to SU with or without metformin) and GetGoal‐L‐Asia (lixisenatide add‐on to basal insulin with or without SU)14, showed that lixisenatide treatment provided glycemic control (decreased HbA1c, FPG and postprandial plasma glucose), and was well tolerated in the Japanese subpopulation22, 23.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Lixisenatide has been studied as monotherapy and in combination with other antidiabetic medications or with basal insulin. 1,[3][4][5][6][7][8][9][10][11][12] The other US Food and Drug Administration (FDA)-approved GLP-1 receptor agonists (albiglutide, dulaglutide, exenatide immediate-release injection, exenatide extended-release injection, and liraglutide) are also indicated as adjunctive therapies to diet and exercise to improve glycemic control in adults with type 2 diabetes mellitus. Each agent has been studied for use as monotherapy and in combination with other antidiabetic medications; however, the current labeling for each advises that these agents are not recommended as first-line therapy for patients inadequately controlled on diet and exercise.…”
Section: Indicationsmentioning
confidence: 99%